The Effect of the Use of Digital-Based Information Systems on User Satisfaction and the Effectiveness of Administrative Data Management at Madrasah Tsanawiyah - Rahmi Fadilah; Rusdinal Rusdinal; Sufyarma Marsidin; Merika Setiawati (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to analyze the effect of using digital-based information systems in Madrasahs on user satisfaction and the effectiveness of administrative data management in Madrasah Tsanawiyah Negeri Padang Pariaman Regency. The research approach is quantitative with survey method. Data were collected through questionnaires and analyzed using statistical tests with Smart PLS Version 3. The results showed that the use of digital-based information systems significantly increased user satisfaction, with Original Sample 0.727, T Statistics 0.733, and P Values 0.034. However, this system does not have a significant effect on the effectiveness of administrative data management, with Original Sample 0.595, T Statistics 0.600, and P Values 0.062. This finding indicates that digital-based information systems are more effective in increasing user satisfaction than the effectiveness of administrative data management. Therefore, system implementation needs to be improved to optimize its benefits on both aspects.